Dr. Allan Bernardo received the Distinguished Service Award - Bernardo, Allan Benedict I. (Animo Repository, 1998)
College of Education Dean Dr. Allan Bernardo received the Distinguished Service Award given by the Psychology Department of the University of Wisconsin-Madison. He was cited for his contribution to the cross-cultural understanding and commitment to the furtherance of psychology as a discipline.